Management of heart failure: evidence versus practice. Does current prescribing provide optimal treatment for heart failure patients? - Hobbs, F (2000)
Heart failure is an increasingly common and costly chronic disorder, with a rising prevalence of at least 2% in populations over the age of 45 years, mortality rates that are as poor as common solid cancers, and very high health care utilisation costs. Despite increased evidence supporting a range of effective interventions, predominantly therapeutic, there remain significant degrees of physician underperformance in terms of heart failure diagnosis and management. Until the early 1990s, the management of heart failure was largely confined to the symptomatic relief of patients with well established heart failure in fluid overload. The introduction of angiotensin-converting enzyme (ACE) inhibitors provided the first treatments that beneficially altered the prognosis of patients with the most common expression of heart failure, namely established systolic dysfunction, whether symptomatic or asymptomatic. Evidence has now extended these benefits to delaying progression of heart failure and reducing hospitalisation. Much of our understanding of the pathophysiology of heart failure stems from these studies. More recent data has clarified the limited role of digoxin, the important benefits of beta-blockade and aldosterone blockers as adjuvants to ACE inhibition, and the emerging evidence on angiotensin II antagonists. There are, in contrast to these positive findings, reliable data from Europe and North America revealing significant underperformance of primary care and hospital physicians in heart failure diagnosis and management, with evidence of underuse and underdosing of evidence-based therapies. Limited qualitative data suggest the reasons for this underperformance are complex and relate to lack of access to objective testing of ventricular function and exaggerated concerns over treatment risks and side-effects. Heart failure represents a complex cluster of aetiologies and risks that are not easy to correctly identify, even in specialist settings. Since there is now powerful evidence on how heart failure can be modified and improved, explicit guidance is needed for which suspected patients should be referred, for confirmation of diagnosis and advice on appropriate treatment regimes, and for which patients can be handled mainly within primary care but with enhanced access to objective non-invasive tests to improve diagnostic reliability and to stratify patients to evidence-based therapies. Current evidence suggests that in North America and Europe today primary care physicians do underperform in their management of patients with heart failure, often owing to factors outside of their immediate control.